Identifikasi Gugus Fungsi Senyawa Hasil Ekstraksi Limbah Kulit Batang Sagu (Metroxylon sagu Rottb L.) dengan Deep Eutectic Solvents Oksalin Menggunakan Spektroskopi FT-IR - Hamdani, Ulfah Zakiyah; Mustawinar, Besse Helmi; Yanti, Rosmalah; Hamdani, Nurul Fuady Adhalia (Universitas Negeri Gorontalo, 2024)
FT-IR spectrum analysis of sago bark waste extract (Metroxylon sagu Rottb L.) which was extracted using deep eutectic solvents (DES) Choline Chloride-Oxalic Acid (Oxaline) has been conducted. DES synthesis was carried out by stirring a number of constituent masses according to the molar ratio at 600 rpm while heating at 60°C. The variation in the molar ratio of DES Oxaline constituents applied were 1:1; 1:1.5; 1:2 and 1:4. Extraction of sago bark waste was carried out by 30 minutes sonication of sago bark waste powder with DES Oxaline solvent at 50W. The sonication results were then centrifuged at 4000 rpm for 35 minutes. The residue was obtained from centrifuge filtration using 1Î¼m filter paper. The synthesized DES Oxaline and its residues were analyzed using FT-IR spectrometry. DES Oxaline which was successfully synthesized were molar ratios of 1:1; 1:1.5 and 1:2. The yield of sago bark waste extracted were 66%; 66% and 62% for 1:1 molar ratio; 1:1.5 and 1:2 respectively. FT-IR spectrum analysis showed that the functional groups of Choline Chloride and Oxalic Acid are depicted in the IR spectrum of Oxaline DES. The residue spectrum analysis stated that the majority of functional groups were representative of lignin.